Metabotropic Glutamate Receptors in Glial Cells: A New Potential Target for Neuroprotection? - Spampinato, Simona Federica; Copani, Agata; Nicoletti, Ferdinando; Sortino, Maria Angela; Caraci, Filippo (Frontiers in Molecular Neuroscience, 2018)
Neurodegenerative disorders are characterized by excitotoxicity and neuroinflammation that finally lead to slow neuronal degeneration and death. Although neurons are the principal target, glial cells are important players as they contribute by either exacerbating or dampening the events that lead to neuroinflammation and neuronal damage. A dysfunction of the glutamatergic system is a common event in the pathophysiology of these diseases. Metabotropic glutamate receptors (mGlus) belong to a large family of G protein-coupled receptors largely expressed in neurons as well as in glial cells They often appear overexpressed in areas involved in neurodegeneration, where they can modulate glutamatergic transmission. Of note, mGlu receptor upregulation may involve microglia or, even more frequently, astrocytes, where their activation causes release of factors potentially able to influence neuronal death. The expression of mGlu receptors has been also reported on oligodendrocytes, a glial cell type specifically involved in the development of multiple sclerosis. Here we will provide a general overview on the possible involvement of mGlu receptors expressed on glial cells in the pathogenesis of different neurodegenerative disorders and the potential use of subtype-selective mGlu receptor ligands as candidate drugs for the treatment of neurodegenerative disorders. Negative allosteric modulators (NAMs) of mGlu5 receptors might represent a relevant pharmacological tool to develop new neuroprotective strategies in these diseases. Recent evidence suggests that targeting astrocytes and microglia with positive allosteric modulators (PAM) of mGlu3 receptor or oligodendrocytes with mGlu4 PAMs might represent novel pharmacological approaches for the treatment of neurodegenerative disorders.